2006
DOI: 10.2190/fbcf-t8vg-l5lj-n8vl
|View full text |Cite
|
Sign up to set email alerts
|

The Death of Princess Diana: The Effects of Memory Enhancement Procedures on Flashbulb Memories

Abstract: This study examined the effects of memory enhancement procedures (i.e., hypnosis, n = 19; context reinstatement/reverse order recall(CR/RO), n = 19; task motivation instructions (TMIs), n = 20) on the fate of flashbulb memories of Princess Diana's death. Three days after Diana's death, participants provided a narrative account and responded to specific questions describing the circumstances under which they learned the news. Eleven to 12 weeks later, participants, selected (from a larger sample, N = 348) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…Free recall responses were coded according to the number of complete ideas and incomplete ideas (Krackow & Lynn, 2003; Krackow, Lynn, & Payne, 2005–2006). For example, the response, ‘We sat on the towel/and then (we‐implied) read a book’ was coded as 2 ideas.…”
Section: Methodsmentioning
confidence: 99%
“…Free recall responses were coded according to the number of complete ideas and incomplete ideas (Krackow & Lynn, 2003; Krackow, Lynn, & Payne, 2005–2006). For example, the response, ‘We sat on the towel/and then (we‐implied) read a book’ was coded as 2 ideas.…”
Section: Methodsmentioning
confidence: 99%
“…Previous researchers have criticized the above work due to the fact that memories being studied were not memories of emotional events. The following study conducted by Krackow, Lynn, and Payne (2006) was the first study to examine the impact of hypnosis on emotional memories of Princess Diana's death. Within 72 hours of Princess Diana's death, undergraduates completed a questionnaire that required them to write a narrative about when they first learned the news of the death as well as respond to specific questions.…”
Section: Hypnosis and Memorymentioning
confidence: 99%
“…" When the open-ended memory reports were examined, Krackow and colleagues (2006) found that hypnotized participants retained less of the detail provided in their original narratives in comparison to other memory enhancement conditions therefore providing additional evidence that hypnosis can be detrimental to recall (Krackow, Lynn, & Payne, 2006). When only flashbulb memory components were abstracted from the narratives, the data showed that hypnotized participants omitted significantly more flashbulb memory components than participants in the other two memory enhancement conditions.…”
Section: Hypnosis and Memorymentioning
confidence: 99%
“…This coding system has been utilized in several memory studies to code free recall data and was developed by Elisa Krackow, PhD (e.g., Krackow Lynn, & Payne, 2005). All free recall data was coded by one coder (the primary researcher), who had established reliability on 25% of the sample with the developer of the coding system and another trained graduate student.…”
Section: Coding and Scoringmentioning
confidence: 99%